MEH-PPV and PCBM Solution Concentration Dependence of Inverted-Type Organic Solar Cells Based on Eosin-Y-Coated ZnO Nanorod Arrays - Riski Titian Ginting; Chi Chin Yap; Muhammad Yahaya; Muhamad Mat Salleh (International Journal of Photoenergy)
The influence of polymer solution concentration on the performance of chlorobenzene- (CB-) and chloroform- (CF-) based inverted-type organic solar cells has been investigated. The organic photoactive layers consisted of poly(2-methoxy-5-(2-ethyl hexyloxy)-1,4-phenylenevinylene) (MEH-PPV) and (6,6)-phenyl C61 butyric acid methyl ester (PCBM) were spin coated from CF with concentrations of 4, 6, and 8 mg/mL and from CB with concentrations of 6, 8, and 10 mg/mL onto Eosin-Y-coated ZnO nanorod arrays (NRAs). Fluorine doped tin oxide (FTO) and silver (Ag) were used as electron collecting electrode and hole collecting electrode, respectively. Experimental results showed that the short circuit current density and power conversion efficiency increased with decrease of solution concentration for both CB and CF devices, which could be attributed to reducing charge recombination in thinner photoactive layer and larger contact area between the rougher photoactive layer and Ag contact. However, the open circuit voltage decreased with decreasing solution concentration due to increase of leakage current from ZnO NRAs to Ag as the ZnO NRAs were not fully covered by the polymer blend. The highest power conversion efficiencies of 0.54 ± 0.10% and 0.87 ± 0.15% were achieved at the respective lowest solution concentrations of CB and CF.